Plesni mojstri Kranjskih deželnih stanov v 18. in 19. stoletju - Podlesnik Tomášiková, Lidija (Muzikološki zbornik, 2011)
The profession of dancing masters substantially influenced the formation of European dancing culture from the 15th century onwards. The Carniolan Provincial Estates provided for the post of dancing master probably for a number of centuries. The present article unveils their activity in Ljubljana in the 18th and 19th century up to the dissolution of the Carniolan Provincial Estates in 1861.
Keywords: 18./19.st.; 18th/19th century; Carniolan Provincial Estates; dancing masters; dancing teachers; družabni ples; Kranjski deželni stanovi; Ljubljana; plesni mojstri; plesni učitelji; social dance